Political research: methods and practical skills - Halperin, Sandra; Heath, Oliver (Oxford University Press, 2020)
"How do I determine my research question? How do I answer my research question? What is data? How do I conduct research in an ethical way? Political Research: Methods and Practical Skills equips you with the knowledge and skills you need to answer questions such as these. Using a step-by-step approach, the authors guide you through the process of asking and answering research questions, and the different methods used in political science. With coverage of both quantitative and qualitative methods, the authors provide advice on how to be critical, rigorous and ethical when both evaluating research findings and conducting your own independent research. The book emphasises how research can impact our ability to answer important political questions, and helps you to learn how to formulate significant questions, make sense of conflicting arguments, and develop your research skills" -- Provided by publisher.